2018
DOI: 10.15567/mljekarstvo.2018.0407
|View full text |Cite
|
Sign up to set email alerts
|

Selection of autolytic lactic acid bacteria as potential adjunct cultures to accelerate ripening of white-brined cheeses

Abstract: The aim of this study was to select lactic acid bacteria (LAB) having autolytic activity on the basis of the technological aspects to accelerate the ripening of white-brined cheeses. For this purpose, mesophilic (n=526) and thermophilic (n=413) LAB isolates were collected from 34 raw milk and 16 cheese samples. 27 LAB isolates with a high autolytic activity ranging from 34 to 54 % were identified by (GTG) 5 fingerprint and 16S rDNA sequence analyses, which showed that Lactococcus lactis and Enterococcus faeciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Moreover, some dead cells underwent autolysis, and the cell content released in the medium was utilized by survivors. Lactic acid bacteria are characterized by differentiated autolytic activity, but the process allows them to eliminate weak or impaired cells from the population [56]. In the mentioned study, L. plantarum strains were autolyzed more than other LAB strains; however, the authors did not test the autolytic activity of L. brevis or L. acidophilus [56].…”
Section: Acrylamide Impact On Lab Viabilitymentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, some dead cells underwent autolysis, and the cell content released in the medium was utilized by survivors. Lactic acid bacteria are characterized by differentiated autolytic activity, but the process allows them to eliminate weak or impaired cells from the population [56]. In the mentioned study, L. plantarum strains were autolyzed more than other LAB strains; however, the authors did not test the autolytic activity of L. brevis or L. acidophilus [56].…”
Section: Acrylamide Impact On Lab Viabilitymentioning
confidence: 90%
“…In the mentioned study, L. plantarum strains were autolyzed more than other LAB strains; however, the authors did not test the autolytic activity of L. brevis or L. acidophilus [56]. It is well known that some lactic acid bacteria can undergo enzymatic cleavage of cell wall peptidoglycans by peptidoglycan hydrolases present in the bacterial cells and that the autolysis depends on factors, such as carbon source, temperature, osmotic concentration, and pH [56]. It has also been demonstrated that N-acetylmuramidase has a critical function in Lactobacillus bulgaricus autolysis [57] as one of the major degraders of the cell wall.…”
Section: Acrylamide Impact On Lab Viabilitymentioning
confidence: 92%
See 1 more Smart Citation
“…It is one of the main desirable characteristics of lactic acid bacteria, especially used as starter cultures, to produce lactic acid and maintain their viability in acidic environment (Leboš Pavunc et al, 2013;Hazır Dalca et al, 2018). Lactic acid bacteria are able to survive in high-acid foods without significant losses in the number of viable microorganisms (Liu et al, 2011).…”
Section: Specific Functional Properties Of Selected Lactic Acid Bacteriamentioning
confidence: 99%